Limited response of primary nasal epithelial cells to Bordetella pertussis infection - Zmuda, Martin; Malcova, Ivana; Pravdova, Barbora; Cerny, Ondrej; Vondrova, Denisa; Kamanova, Jana (Microbiology spectrum, 2025)
Bordetella pertussis is a Gram-negative coccobacillus that causes whooping cough or pertussis, a respiratory disease that has recently experienced a resurgence. Upon entering the respiratory tract, B. pertussis colonizes the airway epithelium and attaches to ciliated cells. Here, we used primary human nasal epithelial cells (hNECs) cultured at the air-liquid interface and investigated their interaction with B. pertussis B1917, focusing on the role of the type III secretion system effector protein BteA. In this model, which resembles the epithelial cells of nasal epithelium in vivo, B. pertussis B1917 localized predominantly in the overlying mucus and scarcely colonized the cell cilia. The colonization led to a gradual decline in epithelial barrier function, as shown by measurements of transepithelial electrical resistance (TEER) and staining of the tight junction protein zonula occludens 1. The decrease in TEER occurred independently of the cytotoxic effector protein BteA. Transcriptomic and proteomic analyses of hNECs showed only moderate changes following infection, primarily characterized by increased mucus production, including upregulation of mucin MUC5AC. No profound response to BteA was detected. Furthermore, the infection did not induce production of inflammatory cytokines, suggesting that B. pertussis B1917 evades recognition by hNECs in this model system. These results suggest that the mucus may serve as a niche that allows B. pertussis B1917 to minimize epithelial recognition and damage. The lack of a robust immune response further indicates that additional components of the nasal mucosa, such as innate immune cells, are likely required to initiate an effective host defense.IMPORTANCEThe nasal epithelium is the initial site where Bordetella pertussis comes into contact with the host during respiratory tract infection. In this study, human nasal epithelial cells cultured at the air-liquid interface were established as an in vitro model to investigate the early stages of B. pertussis infection. We showed that the clinical isolate B. pertussis B1917 resides in the mucus during the early stages of colonization without disrupting the epithelial barrier function. Infection results in moderate transcriptomic and proteomic changes, characterized by increased mucus production and minimal inflammatory signaling. These results suggest that B. pertussis B1917 may evade early host recognition by residing in mucus and avoiding direct interaction with epithelial cells. They also highlight the importance of other components of the mucosal immune system, such as resident immune cells, for the initiation of an effective defense.
Keywords: Bordetella pertussis; kultivované buňky; Cells, Cultured; hlen; lidé; Bacterial Proteins; Virulence Factors, Bordetella; Humans; epitelové buňky; pertuse; BteA effector; Epithelial Cells; Whooping Cough; proteomika; bakteriální proteiny; air-liquid interface culture; airway epithelium; human nasal epithelial cell; faktory virulence rodu Bordetella; mucin 5AC; Mucin 5AC; Proteomics; type III secretion system; nosní sliznice; Mucus; Nasal Mucosa